2015
DOI: 10.1007/s00128-015-1456-1
|View full text |Cite
|
Sign up to set email alerts
|

Combinatorial Biochemical and Chemical Analyses of Polychlorinated Dibenzo-p-dioxins and Dibenzofurans in Agricultural Soils from Chongming Island, Shanghai, China

Abstract: We compared polychlorinated dibenzo-p-dioxin and dibenzofuran (PCDD/F) concentrations [expressed as toxic equivalent quantities (TEQs)] in agricultural soil samples from Chongming Island (Shanghai, China) determined using two analytical approaches, an enzyme-linked immunoassay (EIA) method and a high resolution gas chromatography-high resolution mass spectrometry (HRGC/HRMS) method. The PCDD/F concentrations in all 31 soil samples were at background levels (7.30-16.7 pg EIA-TEQ/g from the EIA analysis and 0.52… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Analytical advantages of HRMS make it broadly applicable to other fields beyond metabolomics and lipidomics. Numerous studies have been published employing HRMS based techniques in many research areas, such as glycomics [ 68 , 69 , 70 ], food science [ 71 , 72 , 73 ], forensics [ 157 ], toxicology [ 157 , 158 ], natural products discovery [ 74 , 75 ], agriculture [ 37 , 96 , 159 , 160 , 161 , 162 , 163 , 164 , 165 , 166 , 167 ], environmental [ 76 , 77 ] and pharmaceutical [ 78 , 79 ] studies. In recent years, food authenticity and safety have become a global concern prompting the development of novel analytical techniques to address food safety issues.…”
Section: Hrms Applications In Metabolomics and Lipidomicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Analytical advantages of HRMS make it broadly applicable to other fields beyond metabolomics and lipidomics. Numerous studies have been published employing HRMS based techniques in many research areas, such as glycomics [ 68 , 69 , 70 ], food science [ 71 , 72 , 73 ], forensics [ 157 ], toxicology [ 157 , 158 ], natural products discovery [ 74 , 75 ], agriculture [ 37 , 96 , 159 , 160 , 161 , 162 , 163 , 164 , 165 , 166 , 167 ], environmental [ 76 , 77 ] and pharmaceutical [ 78 , 79 ] studies. In recent years, food authenticity and safety have become a global concern prompting the development of novel analytical techniques to address food safety issues.…”
Section: Hrms Applications In Metabolomics and Lipidomicsmentioning
confidence: 99%
“…They analyzed plasma, fecal and urine samples from pigs fed high fat or basal regular diets using Ultra High Performance Liquid Chromatography (UHPLC)-HRMS and chemometric analysis and found a set of metabolites most affected by the diet [ 37 , 172 ]. Although the application of metabolomics in environmental studies for the analysis of environmental pollutants has been reported [ 164 , 167 , 173 , 174 , 175 , 176 , 177 , 178 , 179 ], the use of HRMS based MS techniques for environmental research is still limited [ 76 , 77 ]. Applications of mass spectrometry in the pharmaceutical metabolomics can be further expanded by using HRMS (reviewed by Drexler and colleagues [ 78 ]).…”
Section: Hrms Applications In Metabolomics and Lipidomicsmentioning
confidence: 99%